Innovative Application Development of Consumer Loyalty Management Schemes - Aruneshwar D.K; D. Rajasekar D. Rajasekar (International Journal of Supply Chain Management, 2018)
In the current economic conditions, the utilization of present day techniques in innovation project management is a main thrust of development framework improvement. One of the key positions in the advancement extend administration is commercialization of innovative work comes about. The commercialization of innovative work results is unequivocally connected to the marketing of innovations. The primary part of creative promoting is client devotion keeping up. The point of the article is to consider and dissect the likelihood of use the techniques for client dedication administration to the region of inventive project administration, to consider and propose the product items that permits tackling the issue of overseeing consumer loyalty for imaginative projects utilizing the near investigation strategy and technique for expert assessment.